The The Influence of Revenue, Operational Expenses, and Tax Expenses on Financial Performance in Construction Services Companies Listed on The Indonesian Stock Exchange - Irwanto, Endrik; Putra, Aldi Pratama; Fajriyah, Mega; Mulyani, Kartika; Probokusumo, Danny Widyantoro (International Journal of Finance Research, 2024)
This study aims to determine the influence of revenue, operating, and tax expenses on financial performance in construction service companies listed on the Indonesia Stock Exchange in 2017-2020. The variables tested in this study consisted of the influence of income, operating expenses, and tax expenses as independent variables and proxied financial performance with operating profit margin as the dependent variable. The population in this study are construction service companies listed on the Indonesia Stock Exchange for the period 2017-2020. The sampling technique used in this study was purposive sampling, and a sample of 48 data from 12 construction service companies listed on the Indonesia Stock Exchange for the period 2017-2020 that met specific criteria was obtained. The data analysis technique used in this research is panel data regression analysis and classical assumption test. The results of this study indicate that income has a positive and significant effect on the company's financial performance, operating expenses have not a positive and not significant impact on the financial performance of the company, and tax expenses have not a positive and not significant effect financial performance and revenue, operating expenses and tax expense together do have a simultaneous and significant effect on the Company's Financial Performance.